2014
DOI: 10.1002/anie.201406959
|View full text |Cite
|
Sign up to set email alerts
|

Sc(OTf)3‐Catalyzed Bicyclization of o‐Alkynylanilines with Aldehydes: Ring‐Fused 1,2‐Dihydroquinolines

Abstract: A Sc(OTf)3 -catalyzed cascade Prins-type cyclization reaction of o-alkynylanilines, bearing a hydroxy or amine functionality, with aldehydes affords 1,2-dihydroquinoline derivatives having an extra fused ring efficiently under mild reaction conditions. It is interesting to observe the reversed reactivity in the highly selective formation of 1,2-dihydroquinoline derivatives instead of the formation of the usually favored indole derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…These preliminary results indicated that the optimal reaction conditions were as follows: 10 mol% AgSbF 6 in 1,2-dichloroethane at 80 °C (entry 4). This reaction exhibited excellent chemoselectivity: no ring-fused 1,2-dihydroquinoline 3aa′′ was obtained 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These preliminary results indicated that the optimal reaction conditions were as follows: 10 mol% AgSbF 6 in 1,2-dichloroethane at 80 °C (entry 4). This reaction exhibited excellent chemoselectivity: no ring-fused 1,2-dihydroquinoline 3aa′′ was obtained 27 .…”
Section: Resultsmentioning
confidence: 99%
“…5a ). Reaction of 2-iodoaniline with Ts-protected hex-5-yn-1-amine gave the corresponding coupled product, which reacted with 4-methylbenzene-1-sulfonyl chloride to give 1p in 72% yield for the two steps 27 . Exposure of 1p to the optimal difunctionalization reaction conditions afforded 3pk in 73% yield.…”
Section: Resultsmentioning
confidence: 99%
“…34 Ma and Zhu demonstrated the coupling of o-alkynylanilines with a variety of aldehydes to generate 1,2-dihydroquinolines 106 through an alkynyl aza-Prins/intramolecular termination cascade sequence (Scheme 23). 49 Condensation under Lewis acidic conditions leads to distal cyclization onto iminium 105, followed by intramolecular trapping of the developing vinyl cation with the terminal heteroatom nucleophile. In cases where the aromatic aldehyde contains electron-withdrawing substituents, PhCO 2 H aids in the formation of the iminium ion.…”
Section: Scheme 21 N-acyliminium Ion Cyclization With Bromoalkyne Nucmentioning
confidence: 99%
“…A diversity‐orientated approach to complex pyrrolo[1,2‐ a ]quinoline derivatives was achieved through the sequential iron‐catalyzed three‐component coupling of 2‐alkynylanilines, nitroalkenes, and 1,3‐dicarbonyl compounds and a gold(III)‐catalyzed intramolecular hydroarylation reaction . An Sc(OTf) 3 ‐catalyzed (OTf = trifluoromethanesulfonate) cascade Prins‐type cyclization reaction of 2‐alkynylanilines bearing a hydroxy or amine functionality with aldehydes efficiently gave 1,2‐dihydroquinoline derivatives with an extra fused ring under mild reaction conditions . 3‐Aryl‐ and 3‐alkyl‐4(1 H )‐cinnolones were isolated in one step from 2‐aryl‐ or 2‐alkyl(ethynyl)anilines by reactions with sodium nitrite and dilute hydrochloric acid through Richter cyclization .…”
Section: Introductionmentioning
confidence: 99%
“…[16] An Sc(OTf ) 3catalyzed (OTf = trifluoromethanesulfonate) cascade Prins-type cyclization reaction of 2-alkynylanilines bearing a hydroxy or amine functionality with aldehydes efficiently gave 1,2-dihydroquinoline derivatives with an extra fused ring under mild reaction conditions. [17] 3-Aryl-and 3-alkyl-4(1H)-cinnolones were isolated in one step from 2-aryl-or 2-alkyl(ethynyl)anilines by reactions with sodium nitrite and dilute hydrochloric acid through Richter cyclization. [18] Moreover, a BF 3 •OEt 2 -promoted cascade reaction of 2-alkynylanilines with nitriles in the presence of tert-butyl nitrite provided efficient and general access to a variety of 4-amidocinnolines.…”
Section: Introductionmentioning
confidence: 99%